Diabetes Self-Efficacy and Its Relationship with Self-Care and Glycaemic Control Among Elderly Patients with Type 2 Diabetes Mellitus - Mukhopadhyay, Prianka; Biswas, Atanu; Biswas, Gourab (National Journal of Community Medicine, 2023)
Context: Type 2 Diabetes mellitus burden is high in the elderly. Despite effective control measures, complications are aggravated due to lack of self-efficacy. The aim is to assess the role of self-efficacy in influencing self-care and glycaemic control. Methodology: This was an observational, analytical study among elderly diabetics attending Medicine OPD in a tertiary- hospital. 318 patients were enrolled by interviewing every fifth patient on three randomly chosen days per week. Data collection was done using pretested, validated schedule followed by statistical analysis using bivariate, binary logistic and multiple linear regression analysis. Results: Mean age was 59.4 ± 6.5 years, 16.9% patients had glycaemic control. Mean self-efficacy and self-care scores were 5.6 + 3.1 and 2.6 + 1.7 respectively. Multiple linear regression showed higher self-efficacy scores (b =0.14; 95% CI: 0.11, − 0.16), male gender (b =2.01; 95% CI: 0.29-3.74;), glycaemic control (b=-1.81, 95% CI -0.01, - 1.98) and positive family history (b= 3.34; 95% CI 1.23-3.11), were significantly associated with better self-care. Self-efficacy predicted good glycaemic control (AOR= 0.9, SE=0.01; p=0.03) while hypertensives were 2.88 times more likely to have poor glycaemic control (p<0.05). Conclusions: Self-efficacy was positively associated with better self-care and glycaemic control among elderly diabetics.